Transcervical, intrauterine ultrasound-guided radiofrequency ablation of uterine fibroids with the VizAblate® System: three- and six-month endpoint results from the FAST-EU study - Bongers, Marlies (Gynecol Surg, 2014)
This was a prospective, longitudinal, multicenter, single-arm controlled trial, using independent core laboratory validation of MRI results, to establish the effectiveness and confirm the safety of the VizAblate® System in the treatment of symptomatic uterine fibroids. The VizAblate System is a transcervical device that ablates fibroids with radiofrequency energy, guided by a built-in intrauterine ultrasound probe. Fifty consecutive women with symptomatic uterine fibroids received treatment with the VizAblate System. Patients had a minimum Menstrual Pictogram score of 120, no desire for fertility, and met additional inclusion and exclusion criteria. The VizAblate System was inserted transcervically and individual fibroids were ablated with radiofrequency energy. An integrated intrauterine ultrasound probe was used for fibroid imaging and targeting. Anesthesia was at the discretion of each investigator. The primary study endpoint was the percentage change in perfused fibroid volume, as assessed by contrast-enhanced MRI at 3 months. Secondary endpoints, reached at 6 months, included safety, percentage reductions in the Menstrual Pictogram (MP) score and the Symptom Severity Score (SSS) subscale of the Uterine Fibroid Symptom-Quality of Life questionnaire (UFS-QOL), along with the rate of surgical reintervention for abnormal uterine bleeding and the mean number of days to return to normal activity. Additional assessments included the Health-Related Quality of Life (HRQOL) subscale of the UFS-QOL, medical reintervention for abnormal uterine bleeding, and procedure times. Fifty patients were treated, representing 92 fibroids. Perfused fibroid volumes were reduced at 3 months by an average of 68.8 ± 27.8 % (P < 0.0001; Wilcoxon signed-rank test). At 6 months, mean MP and SSS scores decreased by 60.8 ± 38.2 and 59.7 ± 30.4 %, respectively; the mean HRQOL score increased by 263 ± 468 %. There were two serious adverse events (overnight admissions for abdominal pain and bradycardia, respectively) and no surgical reinterventions. These 6-month results suggest that the VizAblate System is safe and effective in providing relief of abnormal uterine bleeding associated with fibroids, with appropriate safety and a low reintervention rate.